Methodologies of the Tābi’īn regarding Derivation of the Quranic Exegesis: Research Study - Dr. Yasir Farooq; Dr. Erum Fatima (jihat-ul-islam, 2022)
In the era of Tabi’īn, three major schools of Qur’anic exegeses were involved in the exegetical services. The first school of Makkah, in which high-ranking personalities like Saeed ibn-e Jubayr, Ikrimah Maula Ibn-e Abbas, and Mujahid ibn-e Jubayr were interested in the interpretation of the Qur’an. The second major school of exegesis was Madinians, where high academic ranks such as Urwa Ibn-e Zubayr, and Sulayman Ibn-e Yasar were nominated. Similarly, the third school was in Kufa, where scholars like Hasan Basri and Qatadah were enlightened with the knowledge of Quranic exegesis. In the article under review, the methodology of Tabi’in has been made the subject of discussion in the interpretation, which has two parts. In the first part, the methods of exegesis derivation of the Tabi’in have been described, as how they obtained the exegesis from their teachers and companions of the Holy Prophet (PBUH). While in the second part, the exegetical method is described. In this regard, first of all, the diversity in Tafsir al Qur’an has been described with examples. Then in Tafsir al-Qur’an with the Sunnah, the methodology was clarified. In which the interpretation of the verses is explained with examples through the ahadith. After this is the statement of the Tafsir al-Qur’an by the companions. Then Tafsir alQur’an by Ijtihad and by language and similar methods of deriving exegesis has been arranged.